Bahasa otomata pada vending machine - Muarief, Fahrurozi (Universitas Tangerang Raya, 2024)
Basically the way the machine works is to receive money input and read the value of the money, then calculate the amount of money that has been entered by the buyer, and delete the item desired by the buyer after the calculation result of the money entered by the buyer is right or more. In creating this machine logic, an automatic theory is needed that explains sequential machines, namely machines that carry out events or events depending on previous events or events. Automated theory is a theory that presents conditions where a device will automatically move towards a certain condition depending on the user's input and the last condition he was in.